Electronic monitoring and administrative empowerment of women leaders in government sectors in Makkah Al-Mukarramah - Al-Mutairi, Alia Zaid Nayef (Journal of Educational and Psychological Sciences, 2021)
This current study aimed at identify the reality of electronic monitoring of women leaders in government sectors in Makkah Al-Mukarramah and to identify the level of administrative empowerment of women leaders in government sectors in Makkah Al-Mukarramah, and to find the relationship between the reality of electronic control and administrative empowerment of women leaders in government sectors in Makkah Al-Mukarramah, the study followed the descriptive approach to its relevance to the nature of The study and its objectives. The study sample consisted of (56) women leaders in government sectors in Makkah Al-Mukarramah. The study highlighted several results, the most important of which were:1.Most of the study sample items are approvals of the reality of electronic monitoring of women’s leaders in government sectors in Makkah Al-Mukarramah, and the most prominent of them is that women’s leaders assume responsibility when an error occurs due to their work in the place.2.Most of the study sample items are approvals of the reality of administrative empowerment of women leaders in government sectors in Makkah Al-Mukarramah. The most prominent of which was the ministry’s confidence in the capabilities of women’s leaders to perform their work efficiently.3.That there is a positive relationship of statistical significance at the level of 0.01 or less between the practice of electronic monitoring and the level of administrative empowerment among women leaders in the government sector in Makkah Al-Mukarramah.The study recommended several recommendations, the most important of which were: Researching the obstacles that limit the level of administrative empowerment of women leaders in government sectors in Makkah and addressing them, and creating an appropriate environment that improves the level of administrative empowerment among women leaders in government sectors in Makkah Al-Mukarramah.
Keywords: Women Leaders; Administrative Empowerment; Electronic Control; Makkah Al-Mukarramah